Factors Influencing Customer’s Repurchase Intention of Go-Jek in Semarang, Indonesia - Mudiantono Mudiantono; Debrina Andhike (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
The emergence of GO-JEK is the beginning of many similar businesses. People are smart enough to compare the benefits that each company offers. Customer dissatisfaction is one of the reasons why people stop using a company’s service. Thus, the company needs to be able to implement strategies in order to keep or increase customer interest in using services offered by GO-JEK. This study aims to analyze how to increase the customers’ intention to repurchase GO-JEK’s services. The method used in collecting data is purposive sampling. This study has 180 samples that were collected through questionnaires. Questionnaires were distributed to the respondents who have ever tried using GO-JEK’s services more than twice in Semarang, Indonesia. The data collected were processed using Structural Equation Modeling (SEM) through AMOS ver. 22.0 to test ten hypothesis. The results show that service quality has a positive and significant effect on brand image, trust, customer satisfaction, and repurchase intention. Price perception also has positive and significant effect on customer satisfaction and repurchase intention. Repurchase intention has also been positively and significantly affected by trust and customer satisfaction. While brand image has a positive but not significant effect on repurchase intention. The results also show that service quality through customer satisfaction has the most significant impact on repurchase intention. Thus, in order to increase repurchase intention, GO-JEK needs to increase service quality and customer satisfaction.